Factors Stimulating Online Buying Behaviour Among Millennials In Pakistan - Ali, Abbasi Ghazanfer (2021)
Online retailing with its increasing foothold has made Pakistan one of the most anticipated destinations for both local and multinational retailers. The success of these online retailers will depend on their ability to attract more and more consumers to shop online. Therefore, it is pertinent to comprehend and understand consumers’ online buying behaviour. The purpose of this research is to examine the factors which can stimulate specific generational cohort’s, i.e. millennials online buying behaviour. The proposed model of this study was conceptualised by using S-O-R theory and Regret theory.